2010
DOI: 10.1021/la904594p
|View full text |Cite
|
Sign up to set email alerts
|

Methylene Blue Incorporation into Alkanethiol SAMs on Au(111): Effect of Hydrocarbon Chain Ordering

Abstract: A detailed polarization modulation infrared reflection absorption spectroscopy, scanning tunneling microscopy, and electrochemical study on methylene blue (MB) incorporation into alkanethiolate self-assembled monolayers (SAMs) on Au(111) is reported. Results show that the amount of MB incorporated in the SAMs reaches a maximum for intermediate hydrocarbon chain lengths (C10-C12). Well-ordered SAMs of long alkanethiols (C > C12) hinder the incorporation of the MB molecules into the SAM. On the other hand, less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 46 publications
4
39
0
3
Order By: Relevance
“…The lipophilic methylene blue (MB) molecule can be incorporated into SAMs. [13] Thus, when the endcharged alkyl chain contains more than 11 methylene groups (see SI 3 in the Supporting Information), H 2 oxidation proceeds only through a MET process, in agreement with Marcus-theory long-range ET. [14] Adsorption of Aa Hase on a 1-butanethiol (C 3 CH 3 ) hydrophobic SAM mimicking the physiological environment unexpectedly results in a majority MET process (Figure 1 c).…”
supporting
confidence: 73%
“…The lipophilic methylene blue (MB) molecule can be incorporated into SAMs. [13] Thus, when the endcharged alkyl chain contains more than 11 methylene groups (see SI 3 in the Supporting Information), H 2 oxidation proceeds only through a MET process, in agreement with Marcus-theory long-range ET. [14] Adsorption of Aa Hase on a 1-butanethiol (C 3 CH 3 ) hydrophobic SAM mimicking the physiological environment unexpectedly results in a majority MET process (Figure 1 c).…”
supporting
confidence: 73%
“…It was concluded that FTIR spectra were registered from free MB molecules [50]. In the high-frequency region of the IR spectrum, the peak at 3015 cm -1 corresponds to vibrations of the CH groups of the heterocycle [22,[51][52][53][54][57][58][59][60].…”
Section: Ftir Spectra Of Mb Gas-phasementioning
confidence: 99%
“…The broad bands at 2979-2929 and 2858 cm -1 correspond to the CH 3 stretching vibrations of the terminal dimethylamino groups [1,7,18,21,22,28,[51][52][53][58][59][60][61][62]. The peaks at 2819 and 2775 cm -1 correspond to the C het -N-(CH 3 ) 2 vibrations [7,18,22,32].…”
Section: Ftir Spectra Of Mb Gas-phasementioning
confidence: 99%
See 1 more Smart Citation
“…A more refined analysis of the position of the CH 2 symmetric and asymmetric stretching bands indicates a structure in which most of the aliphatic chains are elongated and maintain some order. [22,23] X-ray reflectometry (XRR) and grazing-incidence small-angle X-ray scattering (GISAXS) measurements for the same complex have previously shown a highly oriented lamellar structure [15].…”
Section: Membrane Modification and Characterizationmentioning
confidence: 96%